Stable Gastric Pentadecapeptide BPC 157 and Intestinal Anastomoses Therapy in Rats-A Review - Salem Bajramagic; Marko Sever; Fran Rasic; Mario Staresinic; Anita Skrtic; Lidija Beketic Oreskovic; Ivana Oreskovic; Sanja Strbe; Svjetlana Loga Zec; Josip Hrabar; Luka Coric; Matea Prenc; et al. (MDPI AG, 2024)
By introducing the healing of many distinctive anastomoses by BPC 157 therapy, this review practically deals with the concept of the resection and reconnection of the hollow parts of the gastrointestinal tract as one of the cornerstones of visceral surgery. In principle, the healing of quite distinctive anastomoses itself speaks for applied BPC 157 therapy, in particular, as a way in which the therapy of anastomoses can be successfully approached and carried out. Some of the anastomoses implicated were esophagogastric, colocolonic, jejunoileal, and ileoileal anastomoses, along with concomitant disturbances, such as esophagitis, sphincter dysfunction, failed intestinal adaptation, colitis, short bowel syndrome, major vessel occlusion, NO-system, and prostaglandins-system dysfunction, which were accordingly counteracted as well, and, finally, findings concerning other anastomoses healing (i.e., nerve and vessel). Moreover, the healing of fistulas, both external and internal, colocutaneous, gastrocutaneous, esophagocutaneous, duodenocutaneous, vesicovaginal, colovesical, and rectovaginal in rats, perceived as anastomoses made between two different tissues which are normally not connected, may also be indicative. This may be a particular reconnection of the parts of the gastrointestinal tract to re-establish adequate integrity depending on the tissue involved, given that both various intestinal anastomoses and various fistulas (intestinal and skin were accordingly healed simultaneously as the fistulas disappeared) were all healed.